A 1H-NMR based Method for Quantifying Creatinine in Urine Samples from Human Intervention Studies. Issue 5 (2018) - Mueller, Dolores; Kelm, Harald; Ullrich, Sebastian; , Angelika Noll; Richling, Elke
No abstract available